2019
DOI: 10.1186/s40425-019-0586-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of immunomodulatory, antibody-based, oncology therapeutics

Abstract: The increasing use of multiple immunomodulatory (IMD) agents for cancer therapies (e.g. antibodies targeting immune checkpoints, bispecific antibodies, and chimeric antigen receptor [CAR]-T cells), is raising questions on their potential immunogenicity and effects on treatment. In this review, we outline the mechanisms of action (MOA) of approved, antibody-based IMD agents, potentially related to their immunogenicity, and discuss the reported incidence of anti-drug antibodies (ADA) as well as their clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 65 publications
4
101
1
Order By: Relevance
“…PD‐1 antibodies are also immunogenic. Treatment with immune checkpoint inhibitors can result in the development of antidrug antibodies, including antibodies with the potential to neutralize the binding of the checkpoint inhibitor to its ligand although they are currently of unclear clinical significance …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD‐1 antibodies are also immunogenic. Treatment with immune checkpoint inhibitors can result in the development of antidrug antibodies, including antibodies with the potential to neutralize the binding of the checkpoint inhibitor to its ligand although they are currently of unclear clinical significance …”
Section: Discussionmentioning
confidence: 99%
“…Treatment with immune checkpoint inhibitors can result in the development of antidrug antibodies, including antibodies with the potential to neutralize the binding of the checkpoint inhibitor to its ligand although they are currently of unclear clinical significance. 32 Several caveats to the strategies of vial sharing and dose minimization require examination. Cost analyses did not consider the increased drug preparation time (estimated at 3-5 minutes per patient dose) in our pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…An issue with utilizing chimeric mAbs for therapy is potential immunogenicity. Studies have shown the risk of immunogenicity is lower with humanized mAbs versus chimeric mAbs (20). The chimeric mAbs in this comparison contained murine variable domains, and it is not known whether chimeric mAbs with rabbit variable domains have comparable immunogenicity.…”
Section: Introductionmentioning
confidence: 93%
“…Maintaining appropriate levels of mAbs ensures sufficient contact with antigens (e.g., the driving force for diffusion into the tumor) and the subtherapeutic concentrations of mAbs is proposed to cause the inefficacy or acquired resistance [ 45 ]. Also, some mAb drugs have immunogenicity and will stimulate the body to produce antibodies against them, called anti-drug antibody (ADA), to increase their clearance [ 46 ]. Therefore, monitoring mAbs in vivo is pivotal for the best therapeutic outcome.…”
Section: Assessment Of Biological Functionsmentioning
confidence: 99%